Design and Analysis of Closed-Linked Eight-Link Foot Robot with Composite Hinges - Hao Zhang; Jianjun Qin; Xingjie Liu; Lei Jiang (Jixie chuandong)
In view of the complexity of parameters and modeling stratification of the eight-link robot leg configuration mathematical model，a simplest eight-link leg mechanism with composite hinges is proposed. Maintaining the characteristics of the closed-loop kinematic chain，the simplest eight-bar kinematic chain is obtained by local contraction of the general eight-bar kinematic chain，and the robot leg mechanism is designed based on one of the simplest eight-bar linkage mechanisms. The end trajectory curve task point method is used to calculate the size of the leg configuration and the vector ring method is used to carry out the kinematic analysis of the leg mechanism with determined parameters. A simulation model of the robot is established，and a walking simulation analysis of typical ground environment is carried out based on Adams software. On this basis，a prototype is built，and an adaptive walking test is carried out on the actual road，which verifies the feasibility of this configuration. At the same time，it confirms the advantages of the simplest eight-link mechanism with less mathematical parameters and simpler stratification.